2019
DOI: 10.1084/jem.20181554
|View full text |Cite
|
Sign up to set email alerts
|

Krüppel-like factor 3 inhibition by mutated lncRNAReg1cpresults in human high bone mass syndrome

Abstract: High bone mass (HBM) is usually caused by gene mutations, and its mechanism remains unclear. In the present study, we identified a novel mutation in the long noncoding RNA Reg1cp that is associated with HBM. Subsequent analysis in 1,465 Chinese subjects revealed that heterozygous Reg1cp individuals had higher bone density compared with subjects with WT Reg1cp. Mutant Reg1cp increased the formation of the CD31hiEmcnhi endothelium in the bone marrow, which stimulated angiogenesis during osteogenesis. Mechanistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
61
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(64 citation statements)
references
References 51 publications
3
61
0
Order By: Relevance
“…Our previous studies have shown that KLF3 inhibited the expression of JUNB and VEGFA, and further repressed angiogenesis . We also demonstrated that specific knockout of Klf3 in endothelial cells increased the formation of CD31 hi EMCN hi vessels and increased bone formation . Here, we extended our study and confirmed that specific knockout of Klf3 in endothelial cells also could stimulate CD31 hi EMCN hi vessel formation after bone injury and could accelerate bone regeneration.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Our previous studies have shown that KLF3 inhibited the expression of JUNB and VEGFA, and further repressed angiogenesis . We also demonstrated that specific knockout of Klf3 in endothelial cells increased the formation of CD31 hi EMCN hi vessels and increased bone formation . Here, we extended our study and confirmed that specific knockout of Klf3 in endothelial cells also could stimulate CD31 hi EMCN hi vessel formation after bone injury and could accelerate bone regeneration.…”
Section: Discussionsupporting
confidence: 85%
“…Chromatin immunoprecipitation-PCR (ChIP-PCR) assays showed that ophiopogonin D treatment affected the binding of KLF3 to the promoter of JUNB. 23 Western blotting also showed increased protein levels of JUNB and VEGFA in HMECs treated with ophiopogonin D, without affect the expression of KLF3 ( Figure 3H). We further confirmed the angiogenesis stimulating function of ophiopogonin D using migration and tube formation assays.…”
Section: Ophiopogonin D Acts As a Klf3 Inhibitor And Promotes Vessementioning
confidence: 90%
See 2 more Smart Citations
“…Bone homeostasis tightly depends on the balance between bone resorption and bone formation . A perturbation of this balance will lead to some bone metabolic diseases including osteoporosis and osteopetrosis .…”
Section: Introductionmentioning
confidence: 99%